Analysis of Salivary Mycobiome in a Cohort of Oral Squamous Cell Carcinoma Patients From Sudan Identifies Higher Salivary Carriage of Malassezia as an Independent and Favorable Predictor of Overall Survival - Mohamed, Nazar; Litlekalsøy, Jorunn; Ahmed, Israa Abdulrahman; Martinsen, Einar Marius Hjellestad; Furriol, Jessica; Javier-Lopez, Ruben; Elsheikh, Mariam; Gaafar, Nuha Mohamed; Morgado, Luis; Mundra, Sunil; Johannessen, Anne Christine; Osman, Tarig Al-Hadi; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Background: Microbial dysbiosis and microbiome-induced inflammation have emerged as important factors in oral squamous cell carcinoma (OSCC) tumourigenesis during the last two decades. However, the ‘rare biosphere’ of oral microbiome, including fungi, was sparsely investigated. This study aimed to characterize the salivary mycobiome in a prospective Sudanese cohort of OSCC patients and explore patterns of diversities associated with overall survival (OS). Materials and methods: Unstimulated saliva samples (n=72) were collected from patients diagnosed with OSCC (n=59) and non-OSCC control volunteers (n=13). DNA was extracted using combined enzymatic-mechanical extraction protocol. Salivary mycobiome was assessed using next generation sequencing (NGS)-based methodology, by amplifying the ITS2 region. Impact of the abundances of different fungal genera on the survival of OSCC patients was analysed using Kaplan-Meier and Cox regression survival analyses (SPPS). Results: Sixteen genera were identified exclusively in the saliva of OSCC cases. Candida, Malassezia, Saccharomyces, Aspergillus, and Cyberlindnera were the most relatively abundant fungal genera in both groups and showed higher abundance in OSCC patients. Kaplan-Meier survival analysis showed higher salivary carriage of Candida genera significantly associated with poor OS of OSCC patients (p=0.043, Breslow test). In contrast, higher salivary carriage of Malassezia showed significant association with favorable OS in OSCC patients (p=0.039, Breslow test). Cox proportional hazard multiple regression model was applied to adjust both Candida and Malassezia salivary carriage according to age (p=0.029) and identified Malassezia as an independent predictor of OS (hazard ratio = 0.383, CI 95%: 0.16-0.93, p=0.03). Conclusion: Fungal compositional patterns were different in saliva from OSCC patients compared to individuals without OSCC. Fungal genus Malassezia was identified as a putative prognostic biomarker and therapeutical target for OSCC.